معاني غرائب الألفاظ البلاغية في القرآن الكريم عند علماء اللغتين-العربية والماليزية - Zulkipli bin Md. Isa; Hjh Salmah bt. Hj. Ahmad; Md. Nor bin Abdullah; Wan Moharani Mohammad (Design for Scientific Renaissance, 2024)
This study focuses in analysing the meanings of odd rhetorical words in Quran called in Arabic field as Gharaib Al-Alfaz Al-Balaqiyyah which is discussed by Arab and Malay scholars. It involves some sample of chosen words for the purpose of analyzing the perspective of discussions by Arab scholars on the words itself, as well as looking at their differences of view regarding its meanings, before comparing them with its translated meanings given by Malay scholars. This study also aims to give a clear picture in understanding the meanings of these words through an analysis that refers to the most important sources and references in Arabic language. The study also suggested some alternatives for the translation of its meanings in Malay language, and explained the best solutions to cope with the difference opinions given by Arab and Malay scholars regarding its meaning. Hopefully this study will pave the way for researchers and students to seek the best and most accurate meaning of these words in both Arabic and Malay languages. The study found significant differences and disparities in opinion among the scholars in understanding some of the meaning of those words, that shows the need for a deep and thorough study to find the accurate meaning of the words in Malay as well as Arabic Languages.